"Any function on finite lists that is defined by pairing the desired result with the argument list can always be redefined in terms of fold" - haskell

I was reading through the paper A tutorial on the universality and
expressiveness of fold, and am stuck on the section about generating tuples. After showing of how the normal definition of dropWhile cannot be defined in terms of fold, an example defining dropWhile using tuples was proved:
dropWhile :: (a -> Bool) -> [a] -> [a]
dropWhile p = fst . (dropWhilePair p)
dropWhilePair :: (a -> Bool) -> [a] -> ([a], [a])
dropWhilePair p = foldr f v
where
f x (ys,xs) = (if p x then ys else x : xs, x : xs)
v = ([], [])
The paper states:
In fact, this result is an instance of a
general theorem (Meertens, 1992) that states that any function on finite lists that is
defined by pairing the desired result with the argument list can always be redefined
in terms of fold, although not always in a way that does not make use of the original
(possibly recursive) definition for the function.
I looked at Meerten's Paper but do not have the background (category theory? type theory?) and did not quite find how this was proved.
Is there a relatively simple "proof" why this is the case? Or just a simple explanation as to why we can redefine all functions on finite lists in terms of fold if we pair the results with the original list.

Given the remark that you can / may need to use the original function inside, the claim as stated in your question seems trivial to me:
rewriteAsFold :: ([a] -> (b, [a])) -> [a] -> (b, [a])
rewriteAsFold g = foldr f v where
f x ~(ys,xs) = (fst (g (x:xs)), x:xs)
v = (fst (g []), [])
EDIT: Added the ~, after which it seems to work for infinite lists as well.

Related

Changing recursive guards into higher order functions

I'm trying to convert basic functions into higher order functions (specifically map, filter, or foldr). I was wondering if there are any simple concepts to apply where I could see old functions I've written using guards and turn them into higher order.
I'm working on changing a function called filterFirst that removes the first element from the list (second argument) that does not satisfy a given predicate function (first argument).
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst _ [] = []
filterFirst x (y:ys)
| x y = y : filterFirst x ys
| otherwise = ys
For an example:
greaterOne :: Num a=>Ord a=>a->Bool
greaterOne x = x > 1
filterFirst greaterOne [5,-6,-7,9,10]
[5,-7,9,10]
Based on the basic recursion, I was wondering if there might be a way to translate this (and similar functions) to higher order map, filter, or foldr. I'm not very advanced and these functions are new to me.
There is a higher-order function that's appropriate here, but it's not in the base library. What's the trouble with foldr? If you just fold over the list, you'll end up rebuilding the whole thing, including the part after the deletion.
A more appropriate function for the job is para from the recursion-schemes package (I've renamed one of the type variables):
para :: Recursive t => (Base t (t, r) -> r) -> t -> r
In the case of lists, this specializes to
para :: (ListF a ([a], r) -> r) -> [a] -> r
where
data ListF a b = Nil | Cons a b
deriving (Functor, ....)
This is pretty similar to foldr. The recursion-schemes equivalent of foldr is
cata :: Recursive t => (Base t r -> r) -> t -> r
Which specializes to
cata :: (ListF a r -> r) -> [a] -> r
Take a break here and figure out why the type of cata is basically equivalent to that of foldr.
The difference between cata and para is that para passes the folding function not only the result of folding over the tail of the list, but also the tail of the list itself. That gives us an easy and efficient way to produce the rest of the list after we've found the first non-matching element:
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst f = para go
where
--go :: ListF a ([a], [a]) -> [a]
go (Cons a (tl, r))
| f a = a : r
| otherwise = tl
go Nil = []
para is a bit awkward for lists, since it's designed to fit into a more general context. But just as cata and foldr are basically equivalent, we could write a slightly less awkward function specifically for lists.
foldrWithTails
:: (a -> [a] -> b -> b)
-> b -> [a] -> b
foldrWithTails f n = go
where
go (a : as) = f a as (go as)
go [] = n
Then
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst f = foldrWithTails go []
where
go a tl r
| f a = a : r
| otherwise = tl
First, let's flip the argument order of your function. This will make a few steps easier, and we can flip it back when we're done. (I'll call the flipped version filterFirst'.)
filterFirst' :: [a] -> (a -> Bool) -> [a]
filterFirst' [] _ = []
filterFirst' (y:ys) x
| x y = y : filterFirst' ys x
| otherwise = ys
Note that filterFirst' ys (const True) = ys for all ys. Let's substitute that in place:
filterFirst' :: [a] -> (a -> Bool) -> [a]
filterFirst' [] _ = []
filterFirst' (y:ys) x
| x y = y : filterFirst' ys x
| otherwise = filterFirst' ys (const True)
Use if-else instead of a guard:
filterFirst' :: [a] -> (a -> Bool) -> [a]
filterFirst' [] _ = []
filterFirst' (y:ys) x = if x y then y : filterFirst' ys x else filterFirst' ys (const True)
Move the second argument to a lambda:
filterFirst' :: [a] -> (a -> Bool) -> [a]
filterFirst' [] = \_ -> []
filterFirst' (y:ys) = \x -> if x y then y : filterFirst' ys x else filterFirst' ys (const True)
And now this is something we can turn into a foldr. The pattern we were going for is that filterFirst' (y:ys) can be expressed in terms of filterFirst' ys, without using ys otherwise, and we're now there.
filterFirst' :: Foldable t => t a -> (a -> Bool) -> [a]
filterFirst' = foldr (\y f -> \x -> if x y then y : f x else f (const True)) (\_ -> [])
Now we just need to neaten it up a bit:
filterFirst' :: Foldable t => t a -> (a -> Bool) -> [a]
filterFirst' = foldr go (const [])
where go y f x
| x y = y : f x
| otherwise = f (const True)
And flip the arguments back:
filterFirst :: Foldable t => (a -> Bool) -> t a -> [a]
filterFirst = flip $ foldr go (const [])
where go y f x
| x y = y : f x
| otherwise = f (const True)
And we're done. filterFirst implemented in terms of foldr.
Addendum: Although filter isn't strong enough to build this, filterM is when used with the State monad:
{-# LANGUAGE FlexibleContexts #-}
import Control.Monad.State
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst x ys = evalState (filterM go ys) False
where go y = do
alreadyDropped <- get
if alreadyDropped || x y then
return True
else do
put True
return False
If we really want, we can write filterFirst using foldr, since foldr is kind of "universal" -- it allows any list transformation we can perform using recursion. The main downside is that the resulting code is rather counter-intuitive. In my opinion, explicit recursion is far better in this case.
Anyway here's how it is done. This relies on what I consider to be an antipattern, namely "passing four arguments to foldr". I call this an antipattern since foldr is usually called with three arguments only, and the result is not a function taking a fourth argument.
filterFirst :: (a->Bool)->[a]->[a]
filterFirst p xs = foldr go (\_ -> []) xs True
where
go y ys True
| p y = y : ys True
| otherwise = ys False
go y ys False = y : ys False
Clear? Not very much. The trick here is to exploit foldr to build a function Bool -> [a] which returns the original list if called with False, and the filtered-first list if called with True. If we craft that function using
foldr go baseCase xs
the result is then obviously
foldr go baseCase xs True
Now, the base case must handle the empty list, and in such case we must return a function returning the empty list, whatever the boolean argument is. Hence, we arrive at
foldr go (\_ -> []) xs True
Now, we need to define go. This takes as arguments:
a list element y
the result of the "recursion" ys (a function Bool->[a] for the rest of the list)
and must return a function Bool->[a] for the larger list. So let's also consider
a boolean argument
and finally make go return a list. Well, if the boolean is False we must return the list unchanged, so
go y ys False = y : ys False
Note that ys False means "the tail unchanged", so we are really rebuilding the whole list unchanged.
If instead the boolean is true, we query the predicate as in p y. If that is false, we discard y, and return the list tail unchanged
go y ys True
| p y = -- TODO
| otherwise = ys False
If p y is true, we keep y and we return the list tail filtered.
go y ys True
| p y = y : ys True
| otherwise = ys False
As a final note, we cold have used a pair ([a], [a]) instead of a function Bool -> [a], but that approach does not generalize as well to more complex cases.
So, that's all. This technique is something nice to know, but I do not recommend it in real code which is meant to be understood by others.
Joseph and chi's answers already show how to derive a foldr implementation, so I'll try to aid intuition.
map is length-preserving, filterFirst is not, so trivially map must be unsuited for implementing filterFirst.
filter (and indeed map) are memoryless - the same predicate/function is applied to each element of the list, regardless of the result on other elements. In filterFirst, behaviour changes once we see the first non-satisfactory element and remove it, so filter (and map) are unsuited.
foldr is used to reduce a structure to a summary value. It's very general, and it might not be immediately obvious without experience what sorts of things this may cover. filterFirst is in fact such an operation, though. The intuition is something like, "can we build it in a single pass through the structure, building it up as we go(, with additional state stored as required)?". I fear Joseph's answer obfuscates a little, as foldr with 4 parameters, it may not be immediately obvious what's going on, so let's try it a little differently.
filterFirst p xs = snd $ foldr (\a (deleted,acc) -> if not deleted && not (p a) then (True,acc) else (deleted,a:acc) ) (False,[]) xs
Here's a first attempt. The "extra state" here is obviously the bool indicating whether or not we've deleted an element yet, and the list accumulates in the second element of the tuple. At the end we call snd to obtain just the list. This implementation has the problem, however, that we delete the rightmost element not satisfying the predicate, because foldr first combines the rightmost element with the neutral element, then the second-rightmost, and so on.
filterFirst p xs = snd $ foldl (\(deleted,acc) a -> if not deleted && not (p a) then (True,acc) else (deleted,a:acc) ) (False,[]) xs
Here, we try using foldl. This does delete the leftmost non-satisfactory element, but has the side-effect of reversing the list. We can stick a reverse at the front, and this would solve the problem, but is somewhat unsatisfactory due to the double-traversal.
Then, if you go back to foldr, having realized that (basically) if you want transform a list whilst preserving order that foldr is the correct variant, you play with it for a while and end up writing what Joseph suggested. I do however agree with chi that straightforward recursion is the best solution here.
Your function can also be expressed as an unfold, or, more specifically, as an apomorphism. Allow me to begin with a brief explanatory note, before the solution itself.
The apomorphism is the recursion scheme dual to the paramorphism (see dfeuer's answer for more about the latter). Apomorphisms are examples of unfolds, which generate a structure from a seed. For instance, Data.List offers unfoldr, a list unfold.
unfoldr :: (b -> Maybe (a, b)) -> b -> [a]
The function given to unfoldr takes a seed and either produces a list element and a new seed (if the maybe-value is a Just) or terminates the list generation (if it is Nothing). Unfolds are more generally expressed by the ana function from recursion-schemes ("ana" is short for "anamorphism").
ana :: Corecursive t => (a -> Base t a) -> a -> t
Specialised to lists, this becomes...
ana #[_] :: (b -> ListF a b) -> b -> [a]
... which is unfoldr in different clothing.
An apomorphism is an unfold in which the generation of the structure can be short-circuited at any point of the process, by producing, instead of a new seed, the rest of the structure in a fell swoop. In the case of lists, we have:
apo #[_] :: (b -> ListF a (Either [a] b)) -> b -> [a]
Either is used to trigger the short-circuit: with a Left result, the unfold short-circuits, while with a Right it proceeds normally.
The solution in terms of apo is fairly direct:
{-# LANGUAGE LambdaCase #-}
import Data.Functor.Foldable
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst p = apo go
where
go = \case
[] -> Nil
a : as
| p a -> Cons a (Right as)
| otherwise -> case as of
[] -> Nil
b : bs -> Cons b (Left bs)
It is somewhat more awkward than dfeuer's para-based solution, because if we want to short-circuit without an empty list for a tail we are compelled to emit one extra element (the b in the short-circuiting case), and so we have to look one position ahead. This awkwardness would grow by orders of magnitude if, rather than filterFirst, we were to impĺement plain old filter with an unfold, as beautifully explained in List filter using an anamorphism.
This answer is inspired by a comment from luqui on a now-deleted question.
filterFirst can be implemented in a fairly direct way in terms of span:
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst p = (\(yeas, rest) -> yeas ++ drop 1 rest) . span p
span :: (a -> Bool) -> [a] -> ([a], [a]) splits the list in two at the first element for which the condition doesn't hold. After span, we drop the first element of the second part of the list (with drop 1 rather than tail so that we don't have to add a special case for []), and reassemble the list with (++).
As an aside, there is a near-pointfree spelling of this implementation which I find too pretty not to mention:
filterFirst :: (a -> Bool) -> [a] -> [a]
filterFirst p = uncurry (++) . second (drop 1) . span p
While span is a higher order function, it would be perfectly understandable if you found this implementation disappointing in the context of your question. After all, span is not much more fundamental than filterFirst itself. Shouldn't we try going a little deeper, to see if we can capture the spirit of this solution while expressing it as a fold, or as some other recursion scheme?
I believe functions like filterFirst can be fine demonstrations of hylomorphisms. A hylomorphism is an unfold (see my other answer for more on that) that generates an intermediate data structure followed by a fold which turns this data structure into something else. Though it might look like that would require two passes to get a result (one through the input structure, and another through the intermediate one), if the hylomorphism implemented properly (as done in the hylo function of recursion-schemes) it can be done in a single pass, with the fold consuming pieces of the intermediate structure as they are generated by the unfold (so that we don't have to actually build it all only to tear it down).
Before we start, here is the boilerplate needed to run what follows:
{-# LANGUAGE LambdaCase #-}
{-# LANGUAGE DeriveFunctor #-}
{-# LANGUAGE DeriveFoldable #-}
{-# LANGUAGE DeriveTraversable #-}
{-# LANGUAGE TypeFamilies #-}
{-# LANGUAGE TemplateHaskell #-}
import Data.Functor.Foldable
import Data.Functor.Foldable.TH
The strategy here is picking an intermediate data structure for the hylomorphism that expresses the essence of what we want to achieve. In this case, we will use this cute thing:
data BrokenList a = Broken [a] | Unbroken a (BrokenList a)
-- I won't actually use those instances here,
-- but they are nice to have if you want to play with the type.
deriving (Eq, Show, Functor, Foldable, Traversable)
makeBaseFunctor ''BrokenList
BrokenList is very much like a list (Broken and Unbroken mirror [] and (:), while the makeBaseFunctor incantation generates a BrokenListF base functor analogous to ListF, with BrokenF and UnbrokenF constructors), except that it has another list attached at its end (the Broken constructor). It expresses, in a quite literal way, the idea of a list being divided in two parts.
With BrokenList at hand, we can write the hylomorphism. coalgSpan is the operation used for the unfold, and algWeld, the one used for the fold.
filterFirst p = hylo algWeld coalgSpan
where
coalgSpan = \case
[] -> BrokenF []
x : xs
| p x -> UnbrokenF x xs
| otherwise -> BrokenF xs
algWeld = \case
UnbrokenF x yeas -> x : yeas
BrokenF rest -> rest
coalgSpan breaks the list upon hitting a x element such that p x doesn't hold. Not adding that element to the second part of the list (BrokenF xs rather than BrokenF (x : xs)) takes care of the filtering. As for algWeld, it is used to concatenate the two parts (it is very much like what we would use to implement (++) using cata).
(For a similar example of BrokenList in action, see the breakOn implementation in Note 5 of this older answer of mine. It suggests what it would take to implement span using this strategy.)
There are at least two good things about this hylo-based implementation. Firstly, it has good performance (casual testing suggests that, if compiled with optimisations, it is at least as good as, and possibly slightly faster than, the most efficient implementations in other answers here). Secondly, it reflects very closely your original, explicitly recursive implementation of filterFirst (or, at any rate, more closely than the fold-only and unfold-only implementations).

Converting a foldl into fold1

I am using the following fold to get the final monotonically decreasing sequence of a list.
foldl (\acc x -> if x<=(last acc) then acc ++ [x] else [x]) [(-1)] a
So [9,5,3,6,2,1] would return [6,2,1]
However, with foldl I needed to supply a start for the fold namely [(-1)]. I was trying to turn into to a foldl1 to be able to handle any range of integers as well as any Ord a like so:
foldl1 (\acc x -> if x<=(last acc) then acc ++ [x] else [x]) a
But I get there error:
cannot construct infinite type: a ~ [a]
in the second argument of (<=) namely last acc
I was under the impression that foldl1 was basically :
foldl (function) [head a] a
But I guess this isn't so? How would you go about making this fold generic for any Ord type?
I was under the impression that foldl1 was basically :
foldl (function) [head a] a
No, foldl1 is basically:
foldl function (head a) (tail a)
So the initial element is not a list of head a, but head a.
How would you go about making this fold generic for any Ord type?
Well a quick fix is:
foldl (\acc x -> if x<=(last acc) then acc ++ [x] else [x]) [head a] (tail a)
But there are still two problems:
in case a is an empty list, this function will error (while you probably want to return the empty list); and
the code is not terribly efficient since both last and (++) run in O(n).
The first problem can easily be addressed by using pattern matching to prevent that scenario. But for the latter you better would for instance use a reverse approach. Like for instance:
f :: Ord t => [t] -> [t]
f [] = [] -- case when the empty list is given
f a = reverse $ foldl (\acc#(ac:_) x -> if x <= ac then (x:acc) else [x]) [head a] (tail a)
Furthermore personally I am not a huge fan of if-then-else in functional programming, you can for instance define a helper function like:
f :: Ord t => [t] -> [t]
f [] = [] -- case when the empty list is given
f a = reverse $ foldl g [head a] (tail a)
where g acc#(ac:_) x | x <= ac = (x:acc)
| otherwise = [x]
Now reverse runs in O(n) but this is done only once. Furthermore the (:) construction runs in O(1) so all the actions in g run in O(1) (well given the comparison of course works efficient, etc.) making the algorithm itself O(n).
For your sample input it gives:
*Main> f [9,5,3,6,2,1]
[6,2,1]
The type of foldl1 is:
Foldable t => (a -> a -> a) -> t a -> a
Your function argument,
\acc x -> if x<=(last acc) then acc ++ [x] else [x]
has type:
(Ord a) => [a] -> a -> [a]
When Haskell's typechecker tries typechecking your function, it'll try unifying the type a -> a -> a (the type of the first argument of foldl1) with the type [a] -> a -> [a] (the type of your function).
To unify these types would require unifying a with [a], which would lead to the infinite type a ~ [a] ~ [[a]] ~ [[[a]]]... and so on.
The reason this works while using foldl is that the type of foldl is:
Foldable t => (b -> a -> b) -> b -> t a -> b
So [a] gets unified with b and a gets unified with the other a, leading to no problem at all.
foldl1 is limited in that it can only take functions which deal with only one type, or, in other terms, the accumulator needs to be the same type as the input list (for instance, when folding a list of Ints, foldl1 can only return an Int, while foldl can use arbitrary accumulators. So you can't do this using foldl1).
With regards to making this generic for all Ord values, one possible solution is to make a new typeclass for values which state their own "least-bound" value, which would then be used by your function. You can't make this function as it is generic on all Ord values because not all Ord values have sequence least bounds you can use.
class LowerBounded a where
lowerBound :: a
instance LowerBounded Int where
lowerBound = -1
finalDecreasingSequence :: (Ord a, LowerBounded a) => [a] -> [a]
finalDecreasingSequence = foldl buildSequence lowerBound
where buildSequence acc x
| x <= (last acc) = acc ++ [x]
| otherwise = [x]
You might also want to read a bit about how Haskell does its type inference, as it helps a lot in figuring out errors like the one you got.

Haskell Polymorphic definition

I am unable to understand the difference between fold and foldr.
The definition of fold is:
fold :: (t->t->t) -> [t] -> t
fold f [a] = a
fold f (a:b:x)= f a (fold f (b:x))
where there is only one type-parameter t
foldr is defined as
foldr :: (t->u->u) -> u -> [t] -> u
foldr f s [] = s
foldr f s (a:x) = f a (foldr f s x)
I am reading "The craft of functional programming" and it says the fold function is modified by adding an extra argument for the purpose of checking for empty list. This doesn't make sense why there was a need for foldr when the fold function itself could have been modified to serve all the purposes.
Secondly,when I tried the following example from the book:
rev :: [t] -> [t]
rev list = foldr stick [] list
stick :: t -> [t] -> [t]
stick a x = x++[a]
and modified the definition of foldr to foldr::(t->t->t)->[t]->t. Hugs threw an error of inifinite unification type. I tried googling but could not find a satisfactory answer.
so to sum up my doubts are as follows:
doubt1: The reason for making the foldr types to be more general than fold.
doubt2: why do i get an error namely infinitely unification type.
I'll start at the end:
rev :: [t] -> [t]
rev list = foldr stick [] list
stick :: t -> [t] -> [t]
stick a x = x ++ [a]
will work just fine if you use the definition of foldr you gave:
foldr :: (t->u->u) -> u -> [t] -> u
foldr f s [] = s
foldr f s (a:x) = f a (foldr f s x)
as you can see here:
λ> rev [1..5]
[5,4,3,2,1]
what will not work is if you replace it with your definition of fold:
fold :: (t->t->t) -> [t] -> t
no matter how you name it because the trouble start with the signature.
See - when you do rev list = fold stick [] list then you say that
t -> t -> t
should somehow be equal to
t' -> [t'] -> [t']
as the first one is the type fold expects for it's first argument and the second is the signature given by stick (renamed t to t' here to indicate that the types should could be different).
Now this would mean that both t ~ t' and t ~ [t'] or t ~ [t] which is most likely the error you get (btw: a ~ b here is me saying two types a and b should be equal - think = if you like)
This should shed some light on your doubt2 I hope
now to the first part: To be honest I have no clue what I should tell you.
The reason to make fold more general is that then it's more general - indeed foldr is a very special function for lists - it is the list catamorphism (see also wikipedia)
But that's just complicated for general function to operate on lists
Indeed you can rewrite a huge number of functions on list (basically the recursive ones using patter-matching in the empty or cons style) with just foldr - and this will very likely be a big part of your course (I think you are a student of FP101x right?) and of your book - as it's the example for higher-order-functions to rule them all ;)

foldl Implementation with Runtime Errors

Learn You a Haskell explains foldl1:
The foldl1 and foldr1 functions work much like foldl and foldr, only
you don't need to provide them with an explicit starting value. They
assume the first (or last) element of the list to be the starting
value and then start the fold with the element next to it. ...
Because they depend on the lists they fold up having at least one
element, they cause runtime errors if called with empty lists
I figured its implementation is, more or less, the following:
foldl1' :: (a -> a -> a) -> [a] -> a
foldl1' f ys = foldl f (head ys) (tail ys)
But, this potential run-time error troubles me.
Why not implement foldlOption in the following way?
foldlOption :: (a -> a -> a) -> [a] -> Maybe a
foldlOption f [] = Nothing
foldlOption f ys = Just (foldl f (head ys) (tail ys))
REPL
*Main> foldlOption (\acc elem -> if (elem > acc) then elem else acc) []
Nothing
-- find max
*Main> foldlOption (\acc elem -> if (elem > acc) then elem else acc) [1,100,2,3]
Just 100
EDITED
Updated foldl1's and foldlOption's definitions to use tail ys as the last argument to foldl, not ys per Lee Duhem's correction. .
There's actually no good reason why not to do this. Many of the functions in Haskell's prelude like head, tail, init, and many many others fail unnecessarily.
It would be much nicer for them to explicitly note their failure in the types, but that's unfortunately just not what happened when Prelude was standardized and we can't very well change several core functions like head!
Nowadays I recommend simply not using many of these functions and opting for pattern matching, or Gabriel Gonzalez's errors library which provides alternate versions of prelude's partial functions which fail properly.
For example in Control.Error.Safe there's
foldl1Err :: e -> (a -> a -> a) -> [a] -> Either e a
and errors also exports safe, a similar library with Maybe's which has the function
foldl1May :: (a -> a -> a) -> [a] -> Maybe a
exactly like what you wanted :)

Confusion about right folds in Haskell

Just for Background I am a Haskell and FP Beginner, self-learning.
I was going through folds on Learn You a Haskell for great good.
In this I came across this function
map' :: (a -> b) -> [a] -> [b]
map' f xs = foldr (\x acc -> f x : acc) [] xs
Everything is good but as far as I understood the first parameter of the lambda x matches with [] and second acc matches with xs. Right? The confusion starts with the author saying that Then, we prepend it to the accumulator, which is was []. How is the second parameter acc matching with [] which is the first argument? Doesn't make sense.
But his implementation is working while mine (with [] and xs interchanged as parameters) is giving a big error
Practice.hs:88:41:
Couldn't match type `a' with `b'
`a' is a rigid type variable bound by
the type signature for map' :: (a -> b) -> [a] -> [b]
at Practice.hs:87:9
`b' is a rigid type variable bound by
the type signature for map' :: (a -> b) -> [a] -> [b]
at Practice.hs:87:9
Expected type: [b]
Actual type: [a]
In the second argument of `foldr', namely `xs'
In the expression: foldr (\ x acc -> f x : acc) xs []
In an equation for map':
map' f xs = foldr (\ x acc -> f x : acc) xs []
Failed, modules loaded: none.
What am I missing here? Does foldr use flip internally? Or did I just understood it all incorrectly?
The lambda is not applied to [] and xs. Instead it's the first argument to foldr. The second and third arguments to foldr are [] and xs respectively.
It helps to look at what the "symbolic" form of the fold functions looks like. If we have a list of arbitrary elements [b1, b2, b3, b4] and initial element a then:
foldr f a [b1, b2, b3, b4] = f b1 (f b2 (f b3 (f b4 a)))
Conversely the foldl would look like.
foldl f a [b1, b2, b3, b4] = f (f (f (f a b1) b2) b3) b4
This of course ignores the laziness component of the execution, but the general idea still holds.
In your function you fold a function of two arguments which pushes a an element transformed under f onto a cons list.
map' f xs = foldr (\x acc -> f x : acc) [] xs
Expanding this out where (xs=[x0,x1,...,xn]) like above yields:
map' f xs = (f x0 : (f x1 : (f x2 : ... (f xn : []))))
Where the ellipsis is just pseudocode for the all the elements in between. We see is just precisely the element wise map. Hope that helps build intuition.
Begin with the type of foldr, from Hoogle.
foldr :: (a -> b -> b) -> b -> [a] -> b
From this, it is apparent that the second argument of the lambda must match the second argument to foldr, i.e. acc matches [] and x is an element of xs, because the first argument of the lambda has type a, and the third argument of foldr has type [a].
Note that foldl and foldr have different signatures, and hence the arguments in the lambda are swapped.
Might be simplest to just look at the implementation of foldr:
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr k z = go
where
go [] = z
go (y:ys) = y `k` go ys
Then take a simple example like:
foldr (+) 0 [0, 1, 2, 4]
And follow exactly what happens as it recurses and generates the "spine".
Image of a foldr spine:
I'd recommend tracing what happens using pen and paper.
Yet another explanation, using long variable names for effect:
map :: (a -> b) -> [a] -> [b]
map f = foldr step []
where
-- If you have an incomplete solution to your problem, and the first
-- element of the input list, what is the last step you need to finish?
step elem incompleteSolution = f elem : incompleteSolution
The neat thing about using functions like foldr is that when you write your step function, the second argument to step will be the correct result for a smaller version of your problem.
One useful way to think of it is to imagine that foldr has already solved nearly all of your problem, but it's still missing the last step. For example, if you're trying to solve map f (x:xs), picture that foldr has already computed the solution for map f xs. Using that incomplete solution, f and x, what is the final step you need to perform to arrive at the complete solution? Well, as the code snippet illustrates, you apply f to x, and put that in front of the incomplete solution, and you're done.
The magic of foldr is that once you've figured out what to write for step, and what to use for the [] base case, then you're done. Your step function doesn't concern itself with the input list—all it can see is one input list element and an incomplete solution.

Resources